PENGEMBANGAN ALAT EVALUASI MENGGUNAKAN KOMPUTER BERBASIS WONDERSHARE QUIZ CREATOR - Emanuela Utin; Hilarius Jago Duda; Hendrikus Julung (JUTECH : Journal Education and Technology, 2020)
The evaluation tool used in schools is still simple, so it has weaknesses in the assessment process and evaluation activities are not effective. So an interactive evaluation activities are not effective. Soa an interactive evaluation tool and habituation are needed for students because currently the computer-based national exams are. This study aims to produce an evaluation tool using a computer-based wondershare quiz creator on plant networks in class XI IPA SMA Nusantara Indah. The evaluation tool was developed using the Borg and Gall. The researh subjects ware 16 students af class XI IPA. The research instruments ware validation sheets, response questionnaires and learning outcomes tets. The validation results of material experts and media expersts ware 88,4% and 83,86%. The results of the effectiveness of the initial and main field trials of classical learning completeness ware 66,67% and 80%. The results of the quality valid items amounted to 10 questions. The learning outcomes using the wondershare quiz creator tool increased. So that the wondershare quiz creator-based evalution tool was developed worthy of being used as a learning evaluation tool.